Analysis of Vaginal Microbiome in Women with or Without Episodes of Spontaneous Abortion in Eastern Nigeria - Emele, Felix Emele; Onyeulor, Prisca; Nwaokorie, Francisca; Asogwa, Damian (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: Spontaneous abortion (miscarriage) is a common adverse pregnancy outcome earth-wide, and has remained a challenge in Nigeria. This study aimed at comparing the vaginal microbiome of women who have had episodes of spontaneous abortion with those who have not experienced any incident - in order to find out any possible role of vaginal microbiota in spontaneous abortion. STUDY DESIGN: High vaginal swab samples were collected from the vagina fornix of 6 women of reproductive age, with a history of recurrent spontaneous abortion, as well as those without such history (non-spontaneous abortion). The samples were analyzed and interpreted by standard metagenomic and bioinformatic techniques. RESULTS: The following phyla were encountered in spontaneous abortion and non-spontaneous abortion, respectively: Firmicutes (69.4%, 94.9%), Actinobacteria (12.7%, 1.1%), Bacteroidetes (9.5%, 2.8%), Proteobacteria (7.9%, 0.3%), Chloroflexi (0.2%, 0.0%), Fusobacteria (0.2%, 0.0%), Tenericutes (0.02%, 1.0%). There was more bacterial diversity in spontaneous abortion (H=2.34856) than in Non-spontaneous abortion (H=0.61384), with evenness (EH) of 0.60668 and 0.24703, respectively. On the contrary, Lactobacillus had more relative abundance in non-spontaneous abortion (83%) than spontaneous abortion (23.5%). The following genera (among others) occurred exclusively in spontaneous abortion: Enterococcus (relative abundance=26%), Peptostreptococcus (5.1%), Anaerococcus (2.4%), Dialister (2.1%), Streptococcus (1.9%), Megasphaera (1.3%), Mobiluncus (1.0%), Peptinophilus (0.9%), and Veillonella (0.7%). The efficiency of taxonomic identification, using the operational taxonomic unit clustering method, declined, downstream, from family to species levels. CONCLUSION: Recurrent spontaneous abortion appears to be associated with low vaginal Lactobacillus abundance and high bacterial diversity. We recommend that the current operational taxonomic unit -based sequence taxonomic analysis technique be reviewed.